Recovering From COVID-19: A Transatlantic Comparison of Fiscal Policy - Daniel Gros (Intereconomics, 2021)
A chasm has opened up across the Atlantic in terms of fiscal policy.
Keywords: 330; Finanzpolitik; Eurozone; USA